Attitudes and Perceived Social Norms toward Drug Use among Gay and Bisexual Men in Australia. (12th May 2019) - Lea, Toby; Hammoud, Mohamed; Bourne, Adam; Maher, Lisa; Jin, Fengyi; Haire, Bridget; Bath, Nicky; Grierson, Jeffrey; Prestage, Garrett
Abstract: Background: Gay and bisexual men (GBM) report distinctive patterns and contexts of drug use, yet little has been published about their attitudes toward drug use. Objectives: We developed measures of attitudes and perceived social norms toward drug use, and examined covariates of more accepting attitudes and norms among GBM in Australia. Methods: We analyzed baseline data from the Following Lives Undergoing Change (Flux) study. Flux is an online prospective observational study of drug use among Australian GBM. We used principal components factor analysis to generate two attitudinal scales assessing "drug use for social and sexual enhancement" and "perceptions of drug risk." A third perceived social norms scale examined "acceptability of drug use among gay friends." Results: Among 2, 112 participants, 61% reported illicit drug use in the preceding six months. Stronger endorsement of drug use for social and sexual engagement and lower perceptions of drug risk were found among men who were more socially engaged with other gay men and reported regular drug use and drug use for sex. In multivariate analyses, all three scales were associated with recent drug use (any use in the previous six months), but only the drug use for social and sexual enhancement scale was associated with regular (at least monthly) use. Conclusions: Drug use and sex are difficult to disentangle for some GBM, and health services and policies could benefit from a better understanding of attitudinal and normative factors associated with drug use in gay social networks, while recognizing the role of pleasure in substance use.